Direct Influence of Socio-Economic Towards Education Quality: Growth of Standardization - Perales, Roland D.; Familara, Shaira Dane M.; Pena, Ramilyn T. Dela; Mabag, Anna Monica V.; Aban, Emy P.; Martinez, Junecia L.; Mohammad, Nhelbourne K. (The Indonesian Institute of Science and Technology Research, 2023)
Socio-economic is derived from the term socio, which means